Pengaruh Reward, Punishment dan Disiplin Kerja Terhadap Kinerja Pegawai - Maulida Asyifa Salma (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of reward, punishment, and work discipline on employee performance. The research strategy uses quantitative research methods with descriptive analysis. The data collection method is by distributing questionnaires online, which are measured using a Likert scale of one to five. The population of this study were employees of PT Steak Prima Indonesia, Jakarta City. The sampling technique is simple sampling. By using the Slovin formula, there were 109 respondents. The data analysis techniques used in this research are: outer model with calculations Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, and Inner Model with Calculations T statistic, R-Square, f-Square, and VIF, which use the SmartPLS (Partial Least Square) tool version 4.0.9.3. The results of this research show that reward, punishment, and performance appraisal have a positive and significant effect on employee performance.